Complex Bacterial Consortia Reprogram the Colitogenic Activity of Enterococcus faecalis in a Gnotobiotic Mouse Model of Chronic, Immune-Mediated Colitis - Lengfelder, Isabella; Sava, Irina G.; Hansen, Jonathan J.; Kleigrewe, Karin; Herzog, Jeremy; Neuhaus, Klaus; Hofmann, Thomas; Sartor, R. Balfour; Haller, Dirk (Frontiers in Immunology, 2019)
Inflammatory bowel diseases (IBD) are associated with compositional and functional changes of the intestinal microbiota, but specific contributions of individual bacteria to chronic intestinal inflammation remain unclear. Enterococcus faecalis is a resident member of the human intestinal core microbiota that has been linked to the pathogenesis of IBD and induces chronic colitis in susceptible monoassociated IL-10-deficient (IL-10-/-) mice. In this study, we characterized the colitogenic activity of E. faecalis as part of a simplified human microbial consortium based on seven enteric bacterial strains (SIHUMI). RNA sequencing analysis of E. faecalis isolated from monoassociated wild type and IL-10-/- mice identified 408 genes including 14 genes of the ethanolamine utilization (eut) locus that were significantly up-regulated in response to inflammation. Despite considerable up-regulation of eut genes, deletion of ethanolamine utilization (∆eutVW) had no impact on E. faecalis colitogenic activity in monoassociated IL-10-/- mice. However, replacement of the E. faecalis wild type bacteria by a ∆eutVW mutant in SIHUMI-colonized IL-10-/- mice resulted in exacerbated colitis, suggesting protective functions of E. faecalis ethanolamine utilization in complex bacterial communities. To better understand E. faecalis gene response in the presence of other microbes, we purified wild type E. faecalis cells from the colon content of SIHUMI-colonized wild type and IL-10-/- mice using immuno-magnetic separation and performed RNA sequencing. Transcriptional profiling revealed that the bacterial environment reprograms E. faecalis gene expression in response to inflammation, with the majority of differentially expressed genes not being shared between monocolonized and SIHUMI conditions. While in E. faecalis monoassociation a general bacterial stress response could be observed, expression of E. faecalis genes in SIHUMI-colonized mice was characterized by up-regulation of genes involved in growth and replication. Interestingly, in mice colonized with SIHUMI lacking E. faecalis enhanced inflammation was observed in comparison to SIHUMI-colonized mice, supporting the hypothesis that E. faecalis ethanolamine metabolism protects against colitis in complex consortia. In conclusion, this study demonstrates that complex bacterial consortia interactions reprogram the gene expression profile and colitogenic activity of the opportunistic pathogen E. faecalis towards a protective function.